The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1677/joe.0.1580409
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of steroidogenesis by insulin-like growth factors (IGFs) in adult human adrenocortical cells: IGF-I and, more potently, IGF-II preferentially enhance androgen biosynthesis through interaction with the IGF-I receptor and IGF-binding proteins

Abstract: Although the effect of insulin-like growth factors (IGFs) in fetal adrenocortical cells has been investigated extensively, the role of the IGF system in the adult human adrenal gland remains unclear. In the present study we investigated the effect of recombinant human IGF-I and IGF-II on cortisol, dehydroepiandrosterone sulfate (DHEA-S) and cAMP synthesis in adult human adrenocortical cells in primary culture. Both IGFs stimulate basal as well as adrenocorticotropin (ACTH)-induced steroid secretion in a time-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 41 publications
(59 reference statements)
3
41
0
2
Order By: Relevance
“…Given the similarities in signalling between insulin and IGF2 (Pandini et al 2004), we hypothesized that the increased IGF2 in the tumour microenvironment may accelerate prostatic de novo steroidogenesis. IGF2 has been shown to initiate steroidogenesis in thecal (Spicer & Aad 2007) and adrenocortical cells (Fottner et al 1998). In this study, we observed increased IGF2 transcript in clinical tumour samples, which correlated with progression to castrate resistance in addition to increased expression of the receptors that facilitate IGF2 signalling: IGF1R and INSR.…”
Section: Introductionsupporting
confidence: 53%
“…Given the similarities in signalling between insulin and IGF2 (Pandini et al 2004), we hypothesized that the increased IGF2 in the tumour microenvironment may accelerate prostatic de novo steroidogenesis. IGF2 has been shown to initiate steroidogenesis in thecal (Spicer & Aad 2007) and adrenocortical cells (Fottner et al 1998). In this study, we observed increased IGF2 transcript in clinical tumour samples, which correlated with progression to castrate resistance in addition to increased expression of the receptors that facilitate IGF2 signalling: IGF1R and INSR.…”
Section: Introductionsupporting
confidence: 53%
“…Previous studies by our own group and by others have shown a critical role of the IGF system in either normal adrenocortical cells or in adrenocortical tumors , Boulle et al 1998, Fottner et al 1998. Several authors report the effects of high amounts of IGF-II in human adrenal pheochromocytomas on protein and mRNA levels (Hasselbacher et al 1987, Gelato & Vassalotti 1990) despite unaltered levels of IGF-I.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies by our own group and others have shown a critical role for the insulin-like growth factor (IGF) system in either normal adrenocortical cells or adrenocortical tumors , Boulle et al 1998, Fottner et al 1998. In malignant adrenocortical carcinomas, overexpression of IGF peptides (mainly IGF-II), receptors (IGF-IR) and binding proteins (IGFBP-2) has been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Both peptides activate growth-promoting signal transduction pathways by interacting with their receptors, and, to some extent, can also bind to their mutual receptors or to hybrid insulin/IGF-I receptors [9,10]. Other common effects include stimulation of sex steroid synthesis [41][42][43][44][45] and inhibition of SHBG production [24,26,46]. The associations of C-peptide and IGF-I with sex-steroid hormones and SHBG appeared to be independent, as the correlation between the peptides was low and mutual adjustment did not change the relationships with sex-steroid hormones.…”
Section: Insulin and Igf-i: Correlations With Sex-steroid Hormone Conmentioning
confidence: 99%